Economic Valuation and Potential Pollution Load Analysis of Domestic Wastewater in Greater Bandung. Issue 1 (1st July 2022) - Rakhmadi, Adhitya; Suharyanto; Nastiti, Anindrya
Abstract: Sanitation is still a significant problem in most developing countries. The lack of awareness and low education level are the main factors causing 30% of people to still practice open defecation. The problems are getting worse because of the population growth. They are not followed by the availability of sanitation infrastructure and services, leading to people mainly still discharging their domestic wastewater into the river. According to the Ministry of Environment and Forestry (2017), domestic wastewater contributes significantly to Citarum River's pollution by 68. From the calculation of domestic waste pollution estimation potential and analysis using SFD tools, the people in Greater Bandung produced 292 tons of BOD/day (106.580, 25 ton/year), 401, 5 tons of COD/day (131.101 ton/year), and 277, 4 tons of TSS/day (101.251 ton/year). Ironically only 10, 54% of the waste generated are safely managed, and 89, 46% of the rest are unsafely managed. Pollution can cause several problems, including health and some more economic loss. The financial loss of the people of MBR is IDR 4.234.059.114.465/year or IDR 461.543/person/year. The economic loss from the health sector is responsible for about 29% of the total cost, it costs IDR 1.217.720.640.356/year or Rp 148.016/person/year. This is followed by clean water access cost for IDR 3.054.566.638.642/year or IDR 371.289/person/year (71%). This cost is equivalence to 1, 3% of the Gross Domestic Product (GDP) of the people in the Metropolitan Bandung Area.